Quality control of hawthorn tincture by HPTLC method - Khokhlova, K (Annals of Mechnikov’s Institute, 2020)
Introduction. Hawthorn tincture is one of the most used herbal drugs at the domestic pharmaceutical market. According to the State register of drugs at the pharmaceutical market of Ukraine, there are 13 commercial offers of Hawthorn tincture from home-produced manufactures. The initial herbal raw materials for Hawthorn tincture are Hawthorn fruits, which are widespread at the territory of Ukraine. These are pharmacopoeial herbal raw material. Thus, 12 different species of Hawthorn fruits are included into monograph <Hawthorn fruits> of Ukrainian State Pharmacopoeia (SPhU) and State Pharmacopoeia of USSR XI ed. On the territory of Ukraine there are near 30 different species of Hawthorn, and the quantity of species is much arises due to its forms and hybrids. The ‘natural variability’ of bioactive substances of Hawthorn fruits of the same species and possibility of usage of many different species during manufacturing process of herbal drugs lead to the pitfalls in standardization of herbal drugs in general, and Hawthorn tincture particularly, and should be taken in mind while development of its quality control methods. For development of specific and reproducible identification method, it is necessary to ensure the number of parameters: usage of method and equipment that give reproducible results; big selections of different samples; rigorously observation of method’s procedure of implementation. The modern, automated HPTLC method of analysis was chosen for identification purpose. If standardize procedure and suitable equipment are used, the reproducible results of the method have to be obtained. The aim of this paper was development of HPTLC method for identification of Hawthorn tincture, which could be appropriated for stability study and establishment of its expire date. Materials and Methods. In research 13 samples of Hawthorn tinctures from 8 manufactures from Ukraine and Russia were analyzed. These samples were manufactured in 2010, 2014, 2015 years. The research was conducted on the base of CAMAG laboratory, Muttenz, Switzerland. Plates used: HPTLC glass 20x10 cm, Si 60 F254, Merck, Lot: 1.05642.0001. Material used: Automatic TLC Sampler 4, CAMAG; Twin Trough Chamber 20x10 cm, CAMAG; Chromatogram Immersion Device III, CAMAG; TLC Plate Heater III, CAMAG; Automatic Development Chamber ADC 2, CAMAG; Visualizer, CAMAG; TLC Scanner, CAMAG; Filter paper for chamber saturation, CAMAG; Centrifuge EBA21, Hettich; Ultrasonic Bath SW 3H, Sono Swiss; Analytical Balance MS 205 DU, Mettler-Toledo. Chemicals used were pharmacopoeial quality. Reference substances used: hyperoside, USP, batch: 33520F; rutin, EDQM, batch: A0299493; chlorogenic acid, EDQM, batch: A0290470. For identification of Hawthorn tincture by HPTLC the flavonoids were chosen as a group of bioactive substances. The method was developed using format and style of description, which are used for TLC Identification method for Crataegi fructus in European Pharmacopoeia and SPhU. For new identification method of Hawthorn tincture preparation of test solution, reference solutions, system suitability solution (SST), intensity marker, its application, development and results were proposed. For specificity study HPTLC-fingerprints of 13 samples of Hawthorn tinctures, which were produced by manufactures, were compared with HPTLC-fingerprints of laboratory sample of Hawthorn tincture, prepared from properly authentificated herbal raw material of C. laevigata (C. oxyacantha) fructus (solvent – 70% ethanol, ratio – 1:10) and HPTLC-fingerprints of C. laevigata (C. oxyacantha) fructus (solvent – methanol, ratio – 1:10). For reproducible results the research was conducted according to standardized procedure USP <203> High-performance thin-layer chromatography procedure for identification of articles of botanical origin. Visual evaluation of chromatogram of test solutions was conducted with respect to zone position and colour of reference solutions, intensity was evaluated respect to intensity marker of reference solution. Results and Discussion. According to the proposed identification method by HPTLC, the fingerprints of 13 different samples of Hawthorn tincture are quite consistent respect to zone position, color and intensity. All analyzed samples of tinctures are met the requirements of proposed HPTLC-test. Comparison of HPTLC-fingerprints of 13 samples of Hawthorn tincture with the test solutions of laboratory samples of Hawthorn tincture and Crataegi fructus has shown quite similar fingerprints respect to zones position and color. This, prove the specificity of the method. Description of results for developed HPTLC method was given. The tolerance range in fingerprints was specified. Despite of the storage period of Hawthorn tincture is 3 years, the old samples of tincture, which were manufactured in 2010 year are quite similar to new one and would passed proposed HPTLC test. This shows the chemical stability of marker substances of tincture during its storage period. Other investigation in this area is necessary. Conclusion. The specific and reproducible HPTLC identification method of Hawthorn tincture was developed. This could be used as optional/alternative method for conventional TLC. Image on chromatogram of Hawthorn tinctures could be used as a reference image of HPTLC method for Hawthorn tincture and to be included in Pharmacopoeia of Ukraine or any other HPTLC Atlas/Reference book. Developed HPTLC identification method of Hawthorn tincture shown the stability of marker group of bioactive substances (flavonoids) during the expiration period of tincture.